Wittgenstein on Perspicuous Presentations and Grammatical Self-Knowledge - Martin, Christian Georg (Nordic Wittgenstein Review, 2016)
The task of this paper is to exhibit Wittgenstein’s method of perspicuous presentation as aiming at a distinctive kind of self-knowledge. Three influential readings of Wittgenstein’s concept of perspicuous presentation – Hacker’s, Baker’s and Sluga’s – are examined. All of them present what Wittgenstein calls the “unsurveyablity of our grammar” as a result of the “complexity” of our language. Contrary to this, a fundamental difference between matter-of-factual complexity and the unsurveyability of grammar is pointed out. What perspicuous presentations are designed to deal with, isn’t, accordingly, occasioned by the complexity of our language but by an unnoticed assimilation of our own activities as speaking beings to matter-of-factual affairs. In response to this, perspicuous presentations help us to fully appropriate our activities as speakers in virtue of achieving a transparent understanding of the use of “our words”. It thus provides us with a distinctive kind of grammatical self-knowledge.